Evaluation of antioxidant activity of 1,2,4-triazole derivatives in the initiation of free radical processes - Bilai, I. M.; Dariy, V. I.; Khilkovets, A. V.; Bilai, A. I.; Duiun, I. F.; Білай, Іван Михайлович; Дарій, Володимир Іванович; Хільковець, Анастасія Валеріївна; Білай, Андрій Іванович; Дуюн, Ірина Федорівна (Запорізький державний медико-фармацевтичний університет, 2024)
The aim of the study to assess the antioxidant properties of newly synthesized S-derivatives of 1,2,4-triazole through the inhibition of reactive oxygen species accumulation in the superoxide dismutase system. Materials and methods. To achieve this goal, we used one of the methods for assessing antioxidant activity by initiating free radical processes in vitro, specifically by inhibiting the accumulation of reactive oxygen species. Results. Twenty-three S-derivatives of 5-(thiophene-3-ylmethyl)-4-R-1,2,4-triazole-3-thiols were investigated. The most effective compound was sodium 2-((4-phenyl-5-thiophene-3-ylmethyl)-1,2,4-triazole-3-yl)thio)acetate, which exceeded the activity of both reference drugs. Following in activity was compound 22, 1-phenyl-2-((4-phenyl-5-(thiophene-3-ylmethyl)-4H-1,2,4-triazole-3-yl)thio)ethanol, which demonstrated an effect similar to that of emoxipine, while compound 7, 1-(3-fluorophenyl)-2-((5-thiophene-3-ylmethyl)-4H-1,2,4-triazole- 3-yl)thio)ethanone, was slightly less active. Мета роботи – оцінити антиоксидантні властивості нових синтезованих S-похідних 1,2,4-тріазолу через пригнічення накопичення активних форм кисню в системі супероксиддисмутази. Матеріали і методи. Для досягнення мети застосували один із методів оцінювання антиоксидантної активності при ініціюванні вільнорадикальних процесів in vitro, а саме за інгібуванням накопичення активних форм кисню. Результати. Дослідили двадцять три S-похідних 5-(тіофен-3-ілметил)-4-R-1,2,4-тріазол-3-тіолів. На першому місці за силою ефекту – сполука 13 натрію 2-((4-феніл-5-тіофен-3-ілметил)-1,2,4-тріазол-3-іл)тіо)етаноат що перевищує активність обох препаратів порівняння. Наступна за ступенем активності – сполука 22 1-феніл-2-((4-феніл-5-(тіофен-3-ілметил)-4H-1,2,4-тріазол-3-іл)тіо) етан-1-ол, що має наближений ефект до емоксипіну; дещо поступається йому сполука 7 1-(3-фторфеніл)-2-((5-тіофен-3-ілметил)-4Н- 1,2,4-тріазол-3-іл)тіо)етан-1-он.
Оцінювання антиоксидантної активності похідних 1,2,4-тріазолу при ініціюванні вільнорадикальних процесів
Bilai I. M. - ORCID ID: 0000-0002-7574-4093; Dariy V. I. - ORCID ID: 0000-0001-9074-6911; Khilkovets A. V. - ORCID ID: 0000-0001-7401-9458; Bilai A. I. - ORCID ID: 0000-0001-7510-6684; Duiun I. F. - ORCID ID: 0000-0003-1134-2543.
Keywords: 1,2,4-triazole; antioxidant activity; superoxide dismutase; 1,2,4-тріазол; антиоксидантна активністьмутаза; супероксиддис